Current multifunctional albumin-based nanoplatforms for cancer multi-mode therapy - Chang Li; Xin Wang; Hang Song; Shuai Deng; Wei Li; Jing Li; Jin Sun (Elsevier, 2020)
Albumin has been widely applied for rational design of drug delivery complexes as natural carriers in cancer therapy due to its distinct advantages of biocompatibility, abundance, low toxicity and versatile property. Hence, various types of multifunctional albumin-based nanoplatforms (MAlb-NPs) that adopt multiple imaging and therapeutic techniques have been developed for cancer diagnosis and treatment. Stimuli-responsive release, including reduction-sensitive, pH-responsive, concentration-dependent and photodynamic-triggered, is important to achieve low-toxicity cancer therapy. Several types of imaging techniques can synergistically improve the effectiveness of cancer therapy. Therefore, combinational theranostic is considered to be a prospective strategy to improve treatment efficiency, minimize side effects and reduce drug resistance, which has received tremendous attentions in recent years. In this review, we highlight several stimuli-responsive albumin nanoplatforms for combinational theranostic. Keywords: Albumin, Formulations, Multi-mode therapy, Combination therapy, Stimuli-responsive release